Icariin-loaded porous scaffolds for bone regeneration through the regulation of the coupling process of osteogenesis and osteoclastic activity - Xie Y (Dove Medical Press, 2019)
Yuanlong Xie,1,* Wenchao Sun,2,* Feifei Yan,1 Huowen Liu,1 Zhouming Deng,1 Lin Cai11Department of Spine Surgery and Musculoskeletal Tumor, Zhongnan Hospital of Wuhan University, Wuhan City, Hubei Province, People’s Republic of China; 2Department of Pain Management, Wuhan Fourth Hospital, Wuhan City, Hubei Province, People’s Republic of China*These authors contributed equally to this workObjective: Icariin (IC) promotes osteogenic differentiation, and it may be a potential small molecule drug for local application in bone regeneration. Icariin-loaded hydroxyapatite/alginate (IC/HAA) porous composite scaffolds were designed in this study for the potential application of the sustainable release of icariin and subsequent bone regeneration.Methods: An icariin-loaded hydroxyapatite/alginate porous composite scaffold was prepared and characterized by SEM and HPLC for morphology and release behavior, respectively. The mechanical properties, degradation in PBS and cytotoxicity on BMSCs were also evaluated by MTT assay, compression strength and calculation of weight remaining ratio, respectively. Rabbit BMSCs were cocultured with IC/HAA scaffolds, and ALP activity and Alizarin Red staining were performed to evaluate osteogenic differentiation induction. The mRNA and protein expression level of an osteogenic gene was detected by RT-PCR and Western blotting, respectively. In vivo animal models of critical bone defects in the radius of rabbit were used. Four and 12 weeks after the implantation of IC/HAA scaffolds in the bone defect, radiographic images of the radius were obtained and scored by using the Lane and Sandhu X-ray scoring system. Tissue samples were also evaluated using H&E and Masson staining, and an osteogenic gene and Wnt signaling pathway genes were detected.Results: A hydroxyapatite/alginate (HAA) porous composite scaffold-loaded icariin was fabricated using a freeze-drying method. Our data indicated that the icariin was loaded in alginate scaffold without compromising the macro/microstructure or mechanical properties of the scaffold. Notably, the IC/HAA promoted the proliferation of rBMSCs without exerting cytotoxicity on rBMSCs. In vivo, rabbit radius bone defect experiments demonstrated that the IC/HAA scaffold exhibited better capacity for bone regeneration than HAA, and IC/HAA upregulated the relative expression levels of an osteogenic gene and the Wnt signaling pathway genes. Most notably, the IC/HAA scaffold also inhibited osteoclast activity in vivo.Conclusion: Our data suggests a promising application for the use of HAA scaffolds to load icariin and promote bone regeneration in situ through mediation of the coupling processes of osteogenesis induction and osteoclast activity inhibition.Keywords: icariin, bone regeneration, osteogenesis, osteoclastic activity, drug delivery